استخدام منصة إديوكابلاي في مراجعة المفردات العربية وإجراء التدريبات اللغوية لدى طالبات المستوى الإعدادي بمعهد حاجة نورية صبران سوراكارتا - Asma’ Asma’; Aisyah Nanda Hafsuna; Mulyadi Mulyadi (Qawa’id: Jurnal Bahasa dan Sastra Arab, 2026)
This study aims to analyze the use of the Educaplay platform in reviewing Arabic vocabulary among preparatory-level female students at Hajjah Nuriyah Sobron Islamic Institute, Surakarta, and to investigate its role in enhancing classroom interaction and learning motivation. The study employed a qualitative descriptive case study approach based on the researcher's direct teaching experience using the Educaplay platform in Arabic language classes. Data were collected through classroom observations, analysis of interactive learning activities developed on the platform, and a review of relevant literature on educational technology, gamification, and Arabic vocabulary instruction. The findings revealed that the integration of Educaplay transformed vocabulary review from a routine classroom activity into an engaging and interactive learning experience. This implementation significantly increased students' enthusiasm, participation, collaborative learning, and positive competition during classroom activities. Furthermore, the platform's interactive exercises and immediate feedback contributed to improving students' vocabulary retention and their ability to understand and apply vocabulary in appropriate linguistic contexts. The study also found that the effectiveness of Educaplay was determined not by sophisticated technological facilities but by teachers' pedagogical competence in designing meaningful learning activities and managing classroom interaction effectively. Therefore, Educaplay can be considered an effective digital learning platform for supporting Arabic language instruction, particularly in vocabulary review, while simultaneously fostering student motivation and active participation. Future studies are recommended to explore its effectiveness in developing other Arabic language skills across different educational contexts.